Transformasi PGRI Kecamatan Sandai: Sinkronisasi Visi-Misi, Profesionalisme Guru, dan Kebijakan Pendidikan Daerah: The Transformation of the Sandai Sub-district PGRI: Aligning Vision and Mission with Teacher Professionalism and Regional Education Policy - Sudiansyah, Sudiansyah; Siswanto, Siswanto; Jumadi, Jumadi; Henny, Stepanus; Bahroyni, Ahmad; Juhana, Juhana; Rosnawati, Rosnawati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to formulate the institutional transformation of the Sandai Sub-district PGRI (Teachers' Association of the Republic of Indonesia) for the 2025–2030 term, focusing on strengthening its role as a professional teachers' organization in a rural region. The research is grounded in the necessity for teacher organizations to address structural educational challenges in 3T (underdeveloped, frontier, and outermost) regions through a vision, mission, and work programs that are contextually relevant and grounded in local culture. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis involving PGRI administrators, teachers, principals, and education officials. The findings indicate that the institutional transformation of Sandai PGRI is characterized by the strengthening of an inclusive vision, reflective training, the development of learning communities, and advocacy for teacher welfare and professional ethics. These findings affirm PGRI's strategic position as a bridge between national policies and local needs. The implications suggest that the organization must develop a leadership succession (cadre) system, broaden cross-sectoral partnerships, and enhance training grounded in Dayak-Malay cultural values. In conclusion, the Sandai PGRI is positioned to become a model for a progressive, context-aware, and equitable professional teachers' organization, spearheading educational transformation at the local level.